The view of judicial activism and public legitimacy - Mustafa, Cecep (Crime, law and social change, 2021)
The underlying legitimacy issue that underpin sentences related to issues of drug use remains unexplored. It is this relationship between legitimacy and Indonesian judges' accountability when sentencing that this article explores. Judicial activism, and the perceived public legitimacy when sentencing minor drug offenders is presented. To gain an insight into the judicial aim of sentencing minor drug offenders, 31 judges were qualitatively interviewed. Drawing together the findings of judicial activism and public legitimacy, the report concludes that judicial activism is influenced by Islamic culture. Moreover, it finds that Islamic culture is more sympathetic, in comparison with the central government, which is more punitive, with regards to the ways in which the Indonesian judge utilises Islamic culture to support the rehabilitative problem-solving sentences. This report discusses a direct accountability mechanism that is not dissimilar to political accountability in the Anglo-Saxon legal scheme.